Risk and the role of collateral in debt renegotiation - Werner Neus; Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
In his basic model of debt renegotiation, BESTER [1994] argues that collateral is more effective if high risk projects are financed. This result, however, crucially depends on the definition of risk. Using the second-order stochastic dominance criterion introduced by ROTHSCHILD AND STIGLITZ [1970], we show that it is not a project's high risk, induced by a high probability of default, that makes collateral more effective. Instead it turns out that, given the expected return, the probability of default has no impact on the collateral's effectiveness. Moreover, a higher risk of the project caused by a higher loss given default makes the use of collateral even less effective.
urn:nbn:de:bsz:21-opus-57385
Keywords: D81; D82; G21; G32; 330; Debt renegotiation; Collateral; Risk; Stochastic dominance